2020
DOI: 10.1101/2020.04.14.20059733
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct early IgA profile may determine severity of COVID-19 symptoms: an immunological case series

Abstract: SARS-CoV-2 is the causative agent of COVID-19 and is a severe threat to global health.Patients infected with SARS-CoV-2 show a wide range of symptoms and disease severity, while limited data is available on its immunogenicity.Here, the kinetics of the development of SARS-CoV-2-specific antibody responses in relation to clinical features and dynamics of specific B-cell populations are reported. Immunophenotyping of B cells was performed by flow cytometry with longitudinally collectedPBMCs. In parallel, serum sa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 17 publications
(15 reference statements)
3
52
0
1
Order By: Relevance
“…IgA response against SARS-CoV-2 has been reported to be rapid and persistent [ 18 , 19 ] and possibly associated with mucosal immune response in the gut and lungs. Notably, IgA production has been associated with disease severity, suggesting that IgA production might occur locally at the mucosal sites, possibly correlating with the viral load, the duration of the viral exposure and the virus entry route [ 13 , 26 ]. Consistently, a recent communication [ 14 ] confirmed that the highest levels of IgG and IgA antibodies against the Spike S1 domain, encompassing the N-terminal half of the protein with the RBD, were associated with severe disease [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…IgA response against SARS-CoV-2 has been reported to be rapid and persistent [ 18 , 19 ] and possibly associated with mucosal immune response in the gut and lungs. Notably, IgA production has been associated with disease severity, suggesting that IgA production might occur locally at the mucosal sites, possibly correlating with the viral load, the duration of the viral exposure and the virus entry route [ 13 , 26 ]. Consistently, a recent communication [ 14 ] confirmed that the highest levels of IgG and IgA antibodies against the Spike S1 domain, encompassing the N-terminal half of the protein with the RBD, were associated with severe disease [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these predicted epitopes were largely limited to those with sequence homology between SARS-CoV-1 and SARS-CoV-2, given the paucity of available SARS-CoV-2 assay data. Several studies have identified linear B cell epitopes on the SARS-CoV-2 surface glycoprotein from sera of viral exposed patients using peptide arrays [56][57][58] as well as phage immunoprecipitation sequencing (PhIP-Seq) 59 . These studies are an important source of information but their results may include many epitopes from degraded proteins and thus would not be able to promote viral neutralization in vivo due to a lack of surface exposure .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to identifying SARS-CoV-2 T cell epitopes, we sought to identify a set of linear B cell epitopes on the Spike protein which would serve as good targets for stimulating neutralizing antibody responses ( Figure 1 ). Epitope candidates were derived from four published preprint mapping/array studies [56][57][58][59] and one as-of-yet unpublished PEPperCHIP ® peptide array study (for study details see Methods: Antibody epitope curation ). Starting with an initial candidate pool of 58 linear epitopes with data to support in vivo generation in humans ( Figure 4A, Table S4 ), we applied a set of filtering criteria to narrow our target space ( Figure 4B ):…”
Section: B Cell Epitope Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the levels of SARS-CoV-2 antibodies vary widely in patients after recovery, and although infrequently, IgG antibodies could be undetectable in some patients: how these patients recovered without the help of antibodies and whether they were at risk of reinfection of SARS-CoV-2 should be further explored [8]. Soon after disease onset in a mild case, Dahllke observed an increased frequency of plasmablasts concomitantly with a strong SARS-CoV-2-specific IgA response, while a case with more severe progression showed a delayed, but eventually a very strong and broad SARS-CoV-2-specific IgA response [9].…”
Section: Indirect Testmentioning
confidence: 99%